Boosting livestock productivity and sustainability in East Africa: The role of forage seed systems - Burkart, Stefan; Mwendia, Solomon Waweru (2025)
Livestock farming plays a critical role in the economies of East African countries, with millions of people depending on cattle, goats and sheep for food, income and employment. However, despite the region's vast agricultural potential, livestock production faces a significant feed deficit - nearly 40% of the total ruminant feed demand is unmet annually. This challenge, compounded by climate change, is limiting the region's ability to maximize livestock productivity. Addressing this feed shortage is essential for improving food security, rural livelihoods and environmental sustainability.